2019
DOI: 10.1007/s11356-019-06690-x
|View full text |Cite
|
Sign up to set email alerts
|

Solidago canadensis as a bioaccumulator and phytoremediator of Pb and Zn

Abstract: Canadian goldenrod (Solidago canadensis L.) is a plant that grows in a variety of environmental conditions. It shows high capability to spread in various habitats, including fallow lands and brownfield land. The research aimed at analyzing the content of Pb and Zn in the underground (roots, rhizomes) and aboveground parts (stems, leaves, inflorences) of Solidago canadensis (SC) originating from two locations that are clearly different in terms of metal content in soil. Statistically significant differences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…It has also been proposed to be used as a rotation crop as a means of containing noxious weeds in an organic agriculture context [35]. Solidago spp., including S. virgaurea, have been claimed to have potential utility for phytoremediation purposes, based on their ability to transfer iron from soil to plants near iron processing industrial sites [35]; however, studies on other oligo-elements (such as zinc) have not identified particular hyperaccumulator properties for the plant [52], and whereas a number of papers have been published on the phytoremediation potential of S. canadensis [53,54], we could find none on S. virgaurea. The pollen of the latter is of good quality, and its availability may contribute to long-lived bees, able to survive a hard winter [55].…”
Section: Other Usesmentioning
confidence: 61%
See 1 more Smart Citation
“…It has also been proposed to be used as a rotation crop as a means of containing noxious weeds in an organic agriculture context [35]. Solidago spp., including S. virgaurea, have been claimed to have potential utility for phytoremediation purposes, based on their ability to transfer iron from soil to plants near iron processing industrial sites [35]; however, studies on other oligo-elements (such as zinc) have not identified particular hyperaccumulator properties for the plant [52], and whereas a number of papers have been published on the phytoremediation potential of S. canadensis [53,54], we could find none on S. virgaurea. The pollen of the latter is of good quality, and its availability may contribute to long-lived bees, able to survive a hard winter [55].…”
Section: Other Usesmentioning
confidence: 61%
“…Extracts of S. virgaurea contain C6-C1 glycosides (virgaureoside, leiocarposide) and aglycones (vanillic acid, gallic acid) [4,9,[56][57][58], C6-C3 polyphenolic acids (caffeic, chlorogenic, ferulic, synapic, 3-hydroxyphenylacetic acid, 3,4-dihydroxyphenylacetic, homovanilic, acids) [3,9,10,45,[53][54][55][56][57], a number of flavonoid molecules (mostly quercetin and kaempferol glycosides, as well as the free aglycons and small amounts of cyanidin derivatives) [3,4,9,45,49,59,60,[63][64][65][66][67], oleanane-type triterpene saponins [9,[68][69][70][71][72][73][74][75], essential oils containing and monoterpenes (alpha-and beta-pinene, myrcene, limonene, sabinene) [35,[76][77][78][79] and sesquiterpenes (germacrene D β-caryophyllene, α-humulene,), clerodane-type diterpenes [80], polysaccharides [81], and polyacetylenes [82] (tab. 1).…”
Section: Phytochemistrymentioning
confidence: 99%
“…The high tolerance of S. canadensis to soil contaminated with heavy metals and the accumulation of selected metals in the aboveground and underground parts of the plant can be used in the phytoremediation of contaminated soils. In polluted soils, the plant shows a particular tendency to accumulate Pb [Yang et al 2008;Xiang et al 2010;Antonijević et al 2012;Bielecka, Królak 2019a], Cd [Dąbrowska et al 2017], Hg [Tomiyasu et al 2005] and Cu [Antonijević et al 2012;Bielecka, Królak 2019b] in its underground parts. Research carried out in the vicinity of Olkusz, Poland (a region particularly contaminated with Pb and Zn), showed that S. canadensis accumulates, on average, 520 g Pb/ha (maximum about 3,500 g Pb/ha) and about 450 g Zn/ha (max.…”
Section: Positive Aspects Of the Presence Of Canadian Goldenrod In The Environmentmentioning
confidence: 99%
“…Research carried out in the vicinity of Olkusz, Poland (a region particularly contaminated with Pb and Zn), showed that S. canadensis accumulates, on average, 520 g Pb/ha (maximum about 3,500 g Pb/ha) and about 450 g Zn/ha (max. 2,500 g/ha) in its underground parts [Bielecka, Królak 2019a]. Therefore, it can act as a phytostabiliser for these metals.…”
Section: Positive Aspects Of the Presence Of Canadian Goldenrod In The Environmentmentioning
confidence: 99%
See 1 more Smart Citation